Analyzing Visual Metaphor and Metonymy to Understand Creativity in Fashion - Uno, Ryoko; Matsuda, Eiko; Indurkhya, Bipin (Frontiers in Psychology, 2019)
The role of figurative language such as metaphor and metonymy in creativity has been studied in cognitive linguistics. These methods can also be applied to analyze non-linguistic data such as pictures and gestures. In this paper, we analyze fashion design by focusing on visual metaphor and metonymy. The nature of creativity in fashion design has not been fully studied from a cognitive perspective compared to other related fields such as art. We especially focus on fashion design as a communication tool between the designer and audience in conveying a designer’s image of human beings. Photos from two fashion shows were analyzed. We carried out an experiment to compare how human images in two shows are interpreted by those who are familiar with fashion and those who are not. We obtained three results: (1) As far as figurative (metaphorical and metonymic) interpretations of human images are concerned, two groups with different levels of familiarity with fashion had significantly different patterns of responses to two shows. (2) For the non-figurative interpretations (such as physical or personal attributes), no significant difference in the pattern of response to the show was observed between the two groups. However, the participants as a whole responded to the two shows differently. (3) In addition, for the non-figurative interpretations, the fashion experts found significantly more attributes in human images than the other group. The results show that the analysis of figurative interpretations is effective in understanding how familiarity with fashion affects the mode of seeing fashion shows.